Impact of the COVID 19 pandemic on the economic income and expenses of the general dentist - Pares-Ballasco, Giancarlo (2020)
Objective. To determine the opinions of Peruvian dentists regarding the impact of the COVID- 19 pandemic on their income and expenses. Methods. Qualitative study with a phenomenographic focus that used the technique of in-depth interviews with seven dentists in the context of the pandemic during the month of May 2020 in Lima (Peru). The interviews were conducted virtually and the categories included: cost-effectiveness of dental care delivery; perspective on dental care productivity during periods of social isolation and reintegration into routine activities. Results. The dentists interviewed perceive that during this period there has been a reduction in income from dental care delivery, either because of the measures of social restriction established in Peru, or because of the low profitability of emergency and urgent dental treatment. For this reason, the viability of dental care during the period of social isolation has been affected by both, the increase in the conventional budget to provide the service and the additional expenses to comply with new healthcare providers’ guidelines. Conclusions. A decrease in economic income is perceived in dental care, in addition to an increase in economic expenditures during periods of social isolation and reinsertion into routine work activities.